INFORMATIONAL BARRIERS TO ENERGY EFFICIENCY – COMBINING THEORY AND EUROPEAN POLICIES - MORTEN ANDERSEN, Lars; BLEISCHWITZ, Raimund (Journal of Environmental Management and Tourism; Vol 1 No 2 (2010): JEMT Volume I Issue 2(2) Winter 2010, 2016)
This article addresses informational barriers to energy efficiency. It is a widely acknowledged result that an energy efficiency gap exists implying that the level of energy efficiency is at an inefficiently low level. Several barriers to energy efficiency create this gap and the presence of asymmetric information is likely to be one such barrier. The article finds that problems of moral hazard and adverse selection indeed can help explain the seemingly low levels of energy efficiency. The theory reveals two implications to policies on energy efficiency. First, the development of measures to enable contractual parties to base remuneration on energy performance must be enhanced, and second, the information on technologies and the education of consumers and installers on energy efficiency must be increased. Finally, it is found that the preferred EU policy instrument on energy efficiency, so far, seems to be the use of minimum requirements. Less used in EU legislation is the use of measuring and verification as well as the use of certifications. Therefore, it is concluded that the EU should consider an increased use of these instruments.